Addition of Milkfish (Chanos chanos) Bone Meal into the Churros Product - Liliek Soeprijadi; Susi Ratnaningtyas; Fahtia Dwi Cahyani (Jurnal Penelitian Pendidikan IPA, 2024)
Milkfish production in Karawang in 2016 was 19,166 tonnes which resulted in high bone waste. Therefore, there is a need for innovation in the utilisation of milkfish bone meal as a nutritional enhancer for churros products. The purpose of this study was to determine the process flow of making churros with the addition of milkfish bone meal, determine the quality of hedonic test, determine the chemical quality of microbiological levels, determine the appropriate packaging and business analysis of churros. Churros were made in four treatments with formulations F0 without the addition of milkfish bone meal, F1 2.5%, F2 5%, and F3 7.5%. The results showed that hedonic testing of churros with F3 was the best formulation with a moisture content of 5.73%, the highest moisture content was 37.9% in F0. Ash content in F0 0.56%, F1 2.26%, F2 2.83%, F3 4.13. The calcium content in sample F0 was 10.8.99 mg/100g, F3 1470.71 mg/100g. The results of phosphorus testing on churros, sample F0 as much as 982.2 mg / kg, while in F3 has a phosphorus content of 6,516.75 mg / kg. The ALT test results on F0 and F3 churros have met the SNI 8372: 2018 standard with a value of 2.5 x 103 colonies/gram in all samples. The results of the business analysis of milkfish bone meal churros are said to be feasible with a selling price of 45,000 per package.